Magnesium Deficiency Triggers SGR–Mediated Chlorophyll Degradation for Magnesium Remobilization . Issue 1 (9th July 2019) - Peng, Yu Yang; Liao, Li Li; Liu, Sheng; Nie, Miao Miao; Li, Jian; Zhang, Lu Dan; Ma, Jian Feng; Chen, Zhi Chang
Abstract : Mid - aged leaves of rice upregulate OsSGR expression to accelerate chlorophyll degradation for Mg remobilization and photooxidative protection under Mg - limited conditions. Abstract: Magnesium (Mg) is a relatively mobile element that is remobilized in plants under Mg-limited conditions through transport from old to young tissues. However, the physiological and molecular mechanisms underlying Mg remobilization in plants remain poorly understood. In this study, we investigated Mg remobilization in rice ( Oryza sativa ) as facilitated through a Mg dechelatase gene involved in chlorophyll degradation, STAY - GREEN ( OsSGR ). We first observed that mid-aged leaves of rice are more susceptible to Mg deficiency. Expression of OsSGR was specifically upregulated by Mg deficiency, and the response was more pronounced in mid-aged leaves. Knockout of OsSGR exhibited the stay-green phenotype, which hindered the mobility of Mg from mid-aged leaves to young developing leaves. This decline in Mg mobility was associated with inhibited growth of developing leaves in mutants under Mg-limited conditions. Furthermore, Mg deficiency enhanced reactive oxygen species (ROS) generation in mid-aged leaves. ROS levels, particularly hydrogen peroxide, in turn, positively regulated OsSGR expression, probably through chloroplast-to-nucleus signaling, which triggers chlorophyll degradation to protect mid-aged leaves from photodamage. Taken together, these results show that OsSGR-mediated chlorophyll degradation contributes to not only internal remobilization of Mg from mid-aged leaves to developing leaves, but also photooxidative protection of mid-aged leaves under Mg-limited conditions. ROS appear to act as feedback regulators of OsSGR expression to precisely govern chlorophyll degradation in mid-aged leaves where Mg and photosynthetic capacities are relatively high.